2004
DOI: 10.1093/intimm/dxh021
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of NK cell-mediated cytotoxicity to tumor cells by inhibitory NK cell receptor blockers

Abstract: NK cells monitor expression of MHC class I by inhibitory receptors and preferentially kill cells that lose or down-regulate MHC class I expression. One possible mechanism by which tumor cells evade NK cell killing is continued expression of appropriate MHC class I ligands to engage inhibitory receptors on NK cells. We show here that small-mol.-wt blockers against the mouse inhibitory NK cell receptor Ly49A enhance NK cell killing of such tumor cells. We identified Ly49A-binding peptides by selecting phages wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Blocking of MHC class I on Sezary cell lines and fresh Sezary cells, however, enhances or induces their susceptibility to NK lysis, indicating that MHC class I on the malignant target cells participate in their protection, as previously described for leukemic B cells (Palucka et al, 1998). Interestingly, it has been shown that inhibitory NK cell receptor blockers enhance NK cell-mediated killing of tumor cells that are otherwise resistant because of MHC class I expression (Tajima et al, 2004). Nevertheless, with both allogeneic and autologous combinations, we found that MHC class I molecule expression is not sufficient to prevent NK cell lysis completely.…”
Section: Discussionmentioning
confidence: 58%
“…Blocking of MHC class I on Sezary cell lines and fresh Sezary cells, however, enhances or induces their susceptibility to NK lysis, indicating that MHC class I on the malignant target cells participate in their protection, as previously described for leukemic B cells (Palucka et al, 1998). Interestingly, it has been shown that inhibitory NK cell receptor blockers enhance NK cell-mediated killing of tumor cells that are otherwise resistant because of MHC class I expression (Tajima et al, 2004). Nevertheless, with both allogeneic and autologous combinations, we found that MHC class I molecule expression is not sufficient to prevent NK cell lysis completely.…”
Section: Discussionmentioning
confidence: 58%
“…It has also been observed in in vitro studies that a blockage of KIR markedly increases CTL-mediated killing of HIV-infected, autologous cells [40]. In mice, which do not have KIR genes but express their functional orthologs (LY49 genes) on their NK cells and a subset of CTL, it was also demonstrated that blockage of LY49 receptors increases anti-tumor activities of NK cells resulting in tumor regression [142,143]. Interestingly iKIR, CD94/NKG2, and KLR-G1 could also be detected but sparsely on CD4 ϩ T cells in human peripheral blood.…”
Section: Changing the Expression Of Nkrs On Non-nk Cellsmentioning
confidence: 94%
“…One strategy to enhance NK cell activity is to block these inhibitory receptors and allow ‘missing-self’ recognition to occur. Studies using mAbs or small molecular weight inhibitors to block murine inhibitory Ly49 receptors or human killer-cell immunoglobulin-like receptors (KIR) showed the potential of generating anti-tumor immunity by releasing a brake on NK cell activity [1923]. In certain conditions, such as a growing tumor, the expression of ligands for inhibitory receptors can be reduced, and the lack of inhibitory signals may allow activation of NK cells [24].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%